IMPLEMENTATION OF THEMATIC LEARBING BASED ON HOTS (HIGHER OF ORDER THINKING SKILLS) IN 2013 CURRICULUM AT SD MUHAMMADIYAH 05 BATU - Tyas Deviana (Nurul Jadid University, 2019)
Learning in the 2013 curriculum uses a thematic approach that integrates several content lessons in a theme and sub-theme (except for high classes, for separate Mathematics and PJOK content). The implementation of thematic learning at elementary school level is due to the characteristics and mindset of students that are holistic and concrete operational. The thematic learning process places more emphasis on students' thinking abilities in analyzing a problem, not just being able to answer right and wrong. This is very related to HOTS (Higher of Order Thinking Skills) based learning which emphasizes high-level thinking skills. SD Muhammadiyah 5 Batu is one of the elementary schools that has implemented a 2013 curriculum that applies a thematic approach. Based on the results of interviews with the Principal it was found that SD Muhammadiyah had conducted workshops and assisted in the preparation of HOTS-based thematic learning tools. The purpose of this study is to analyze the planning, implementation, assessment of HOTS learning, as well as the relationship between planning, implementation, and assessment in a good learning.